Experimental platform to facilitate novel back brace development for the improvement of spine stability. Issue 15 (18th November 2019) - Cooper, L.; Gullane, A.; Harvey, J.; Hills, A.; Zemura, M.; Martindale, J.; Rennie, A.; Cheneler, D.
Abstract: The spine or 'back' has many functions including supporting our body frame whilst facilitating movement, protecting the spinal cord and nerves and acting as a shock absorber. In certain instances, individuals may develop conditions that not only cause back pain but also may require additional support for the spine. Common movements such as twisting, standing and bending motions could exacerbate these conditions and intensify this pain. Back braces can be used in certain instances to constrain such motion as part of an individual's therapy and have existed as both medical and retail products for a number of decades. Arguably, back brace designs have lacked the innovation expected in this time. Existing designs are often found to be heavy, overly rigid, indiscrete and largely uncomfortable. In order to facilitate the development of new designs of back braces capable of being optimised to constrain particular motions for specific therapies, a numerical and experimental design strategy has been devised, tested and proven for the first time. The strategy makes use of an experimental test rig in conjunction with finite element analysis simulations to investigate and quantify the effects of back braces on flexion, extension, lateral bending and torsional motions as experienced by the human trunk. This paper describes this strategy and demonstrates its effectiveness through the proposal and comparison of two novel back brace designs.